2014
DOI: 10.1007/s11010-014-2297-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of norfloxacin and moxifloxacin on melanin synthesis and antioxidant enzymes activity in normal human melanocytes

Abstract: Fluoroquinolone antibiotics provide broad-spectrum coverage for a number of infectious diseases, including respiratory as well as urinary tract infections. One of the important adverse effects of these drugs is phototoxicity which introduces a serious limitation to their use. To gain insight the molecular mechanisms underlying the fluoroquinolones-induced phototoxic side effects, the impact of two fluoroquinolone derivatives with different phototoxic potential, norfloxacin and moxifloxacin, on melanogenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Previous studies have demonstrated that fluoroquinolones, including lomefloxacin (33), norfloxacin and moxifloxacin (34) and sparfloxacin (35) may alter the activity of the cellular antioxidant enzymes superoxide dismutase, catalase and GSH peroxidase. It has therefore been hypothesized that fluoroquinolones may induce cellular oxidative stress by triggering the generation of ROS, particularly the superoxide radical anion and hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that fluoroquinolones, including lomefloxacin (33), norfloxacin and moxifloxacin (34) and sparfloxacin (35) may alter the activity of the cellular antioxidant enzymes superoxide dismutase, catalase and GSH peroxidase. It has therefore been hypothesized that fluoroquinolones may induce cellular oxidative stress by triggering the generation of ROS, particularly the superoxide radical anion and hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no previous studies investigating the effect of fluoroquinolones on human TNBC cells. It is hypothesized that fluoroquinolones inhibit bacterial type II topoisomerase (DNA gyrase), however there is also evidence to suggest that they may affect the viability of cells, including cancer cells (12,13,(33)(34)(35). The anticancer activity of topoisomerase inhibitors may potentially occur via the inhibition of mitochondrial DNA synthesis, which subsequently induces mitochondrial injury, disorders in the respiratory chain and depletion of intracellular ATP stores.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase activity was estimated by measuring the rate of oxidation of L ‐DOPA to DOPAchrome as previously described . The enzymatic assay was initiated by the addition of 40 μL of L ‐DOPA solution (2 mg/mL) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Tyrosinase activity was estimated by measuring the rate of oxidation of L-DOPA to DOPAchrome as previously described. 21,22 The enzymatic assay was initiated by the addition of 40 μL of L-DOPA solution (2 mg/mL) at 37°C. The absorbance of DOPAchrome was measured every 10 minutes for at least 1.5 hours at 475 nm using a microplate reader.…”
Section: Tyrosinase Activitymentioning
confidence: 99%
“…The use of sparfloxacin (SPFX), a third-generation fluoroquinolone antibiotic, is widespread in animals for preventing disease and promoting growth due to its broad-spectrum antibacterial properties (Peng et al, 2016). A deficiency in SPFX leads to phototoxicity, renal-hepatic system damage, and genotoxicity (Beberok et al, 2015;Giacometti, Cirioni, Barchiesi, & Scalise, 2000). Furthermore, long-term exposure to SPFX can result in the emergence of drug-resistant pathogens which increases the risk of death from common infections (Martín-Galiano & de la Campa, 2003;Minnick, Wilson, Smitherman, & Samuels, 2003;Tlili et al, 2016;Weigel, Anderson, & Tenover, 2002).…”
Section: Introductionmentioning
confidence: 99%